The Effect of Shelter on Semen Quality of âPeranakan Ettawaâ Goat - Qisthon, A; Suharyati, S (ANIMAL PRODUCTION, 2007)
The experiment was conducted to study the effect of shelter on semen quality of Peranakan Ettawa (PE) Goats Eight PE goats were allocated into cross over design. Four PE goats were placed under no shelter (09.00-14.30) and another one was placed under shelter. The results of this research showed that semen volume, sperm motility, sperm concentration, and live sperm percentage of PE goat under shelter were higher (P<0.01) than those of PE goat under no shelter. On the other hand, sperm abnormality of PE goat under shelter was lower (P<0.01) than that of PE goat under no shelter. It was concluded that the use of shelter could improve semen quality. (Animal Production 9(2): 73-78 (2007) Key Words : Shelter, semen, goat